Konsep Lima Kekuatan Porter untuk Membedah Kondisi Industri Rotan Indonesia (The Concept of Porter‘s Five Forces in Evaluating Indonesian Rattan Industry) - Lisman Sumardjani (Institut Pertanian Bogor (IPB University), 2009)
Rattan is one of non timber product forest which is very famous in Indonesia. Indonesia has 350 from the total of 600 rattan species in the world. Indonesia rattan potential is getting more significant when it is known that among 350 species, only 53 species have been traded in both local and international market. Recently, Indonesia rattan industry facing some serious conditions, such as decreasing raw rattan production, dropping export volume and value of rattan product, and popping out the imitation rattan. Improper policy of government, by closing and opening the export the half-finished product of rattan without comprehensive consideration and analyzing become active catalyst of falling down for Indonesia rattan industry. Whereas in “Porter’s Five Forces” concept which was written by Michael Porter (1980), it was stated that the material component is one of five industrial environmental conditions. This concept can be used to analyze industry and company strategy development for looking at market interest. Based on this concept, Indonesia has potential advantage as world’s main rattan supplier, because rattan can not be found in other place, except a little one. In application stage, there are some steps can be done to return the glory of rattan, namely: assuring the market of round-semi finished rattan product is opened widely, guarantying the rattan product which has strong competitive value through design development and production cost efficiency, and national campaign to increase the usage of rattan product.Keywords: rattan, raw material, supplier, Porter’s five forces, market